High-intensity interval training on unstable vs stable surfaces: effects on explosive strength, balance, agility, and Tsukahara vault performance in gymnastics - Khaled Abuwarda; Mostafa Mansy; Mohamed Megahed (IP Iermakov S.S., 2024)
Background and Study Aim. This study compares the effects of high-intensity interval training (HIIT) on unstable and stable surfaces on explosive strength, balance, agility, and Tsukahara vault performance in gymnastics. Material and Methods. A nonrandomized trial study was conducted on twenty-seven well-trained male vault players who were assigned into 3 equal groups, a HIIT unstable group (UG), a HIIT stable group (SG), and the control group (CG). The training period for the subjects lasted eight weeks, with 3 sessions each week. All of the aforementioned variables were assessed both before and after the training period. Results. The main findings indicate that both UG and SG showed greater improvement than the CG on explosive strength, balance, agility, and Tsukahara vault performance in gymnastics (ES= 0.52 to 0.68, P<0.05). In addition, there were significant differences between the UG and SG in explosive strength, balance and Tsukahara vault performance (P<0.05) favoring UG, while no significant differences between UG and SG in agility. However, the UG as compared to the SG in agility had only limited additional effects. The UG and SG significantly increased all tests from pre- to post-test (ES= 1.10 to 4.78, 0.98 to 3.53), respectively (P<0.05). The CG significantly increased the explosive strength and Tsukahara vault performance tests from pre- to post-test ((ES= 0.77 to 0.78, P <0.05), while there were no significant differences in the balance and agility tests (P > 0.05). Conclusions. Accordingly, HIIT with unstable surfaces can be used as an alternative method to improve explosive strength and balance. Also, it can be used alongside stable surface exercises when developing agility.